FAUNA OF CLICK BEETLES (COLEOPTERA ELATERIDAE) OF THE KIZLYAR DISTRICT OF DAGESTAN - G. A. Dzhafarova (Юг России: экология, развитие, 2014)
Results of research of bugs are given in work Elateridae the Kizlyar area: specific structure, quantity of copies. Data on distribution.